Charles Fahy papers - Fahy, Charles, 1892-1979.
Diaries (1918-1949), family and general correspondence, legal case files, subject files, speeches and writings, and other papers. The bulk of the collection consists of Fahy's case files while serving on the U.S. Court of Appeals for the District of Columbia Circuit, documenting a number of notable decisions in civil and criminal law, 1949-1976, Other papers relate to Fahy's role as an advisor to and representative of the presidential administrations of Franklin D. Roosevelt, Harry S. Truman, Dwight D. Eisenhower, John F. Kennedy, and Lyndon B. Johnson, including his negotiations on lend-lease operations with Great Britain in 1941, his work on the Committee Appointed to Review the Decartelization Program in Germany (Ferguson Commission) that oversaw the disolution of industrial production there following World War II, and his chairmanship of the President's Committee on Equality of Treatment and Opportunity in the Armed Services (1948-1950). Also documented are Fahy's affiliations with the American Bar Association, Bar Association of the District of Columbia, Georgetown University, and the University of Notre Dame; his practice of law in Washington, D.C., and Santa Fe, N.M.; and his World War I experience as a naval aviator. Fahy (Fahey) family papers include correspondence, naturalization papers of his father, Thomas Fahy, and reminiscences and photograph relating to the death of Ellen Axson Wilson. Principal correspondents include Felix Frankfurter, Theodore Martin Hesburgh, Philip Levy, Joseph O'Meara, Simon E. Sobeloff, and Harry S. Truman.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Jurist, lawyer, U.S. solicitor general, and U.S. delegate to the United Nations.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Eisenhower, Dwight D. -- 1890-1969.; Fahey family; Fahy, Thomas, -- 1844-1917.; Frankfurter, Felix, -- 1882-1965 -- Correspondence; Hesburgh, Theodore Martin, -- 1917- -- Correspondence; Johnson, Lyndon B. -- 1908-1973.; Kennedy, John F. -- 1917-1963.; Levy, Philip, -- -1970 -- Correspondence; O'Meara, Joseph, -- 1898- -- Correspondence; Roosevelt, Franklin D. -- 1882-1945.; Sobeloff, Simon Ernest, -- 1894-1973 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Wilson, Ellen Axson; Committee Appointed to Review the Decartelization Program in Germany (U.S.); United Nations; United States. -- Court of Appeals (District of Columbia Circuit); United States. -- President's Committee on Equality of Treatment and Opportunity in the Armed Services; American Bar Association; Bar Association of the District of Columbia; Georgetown University; University of Notre Dame; Cartels -- Germany; Civil law -- United States; Courts -- Washington (D.C.); Criminal law -- United States; Industries -- Germany; Lend-lease operations (1941-1945); Practice of law -- New Mexico -- Santa Fe; Practice of law -- Washington (D.C.); World War, 1914-1918 -- Aerial operations, American; Germany -- History -- 1945-1955.; Great Britain -- Foreign relations -- United States; United States -- Foreign relations -- Great Britain; United States -- Politics and government -- 1945-; United States -- Politics and government -- 1933-1945.; Jurists; Lawyers; Public officials